Blockchain based Real Estate using Smart Contracts - Ryan Fernandes; Andrew Fernandes; Himani Jawale (International Journal of Engineering and Management Research, 2020)
In today’s world global real estate investments have taken over more than twice the size of the stock market. Even after the dominance of the real estate market there are still a less number of investors due to liquidity and global access to sensitive or critical information. Due to various flaws in security in the current system, the tenants and owners are barely satisfied. The main focus of this paper is to incorporate the use of blockchain in the current real estate market and represent the facilities and advantages it can give to the real estate market. Blockchain based real estate is better because each block contains a cryptic hash of the previous record, a timestamp and transaction data which makes it difficult to forge documents and sensitive information of the investor. Another advantage of blockchain is that it is resistant to any type of data modification. Blockchain technology can sort out the security issues and forgery incidents that are faced by the real estate market. Also blockchain provides much meaningful assets and insights to the real estate market at a reasonable and stable-priced market. The proposed solution for the selected problem statement is Tokenizing real estate assets refers to a process in which a property owner can offer digital tokens that represent a share of their property. Using a blockchain to track these investments, with each transaction being time-stamped and immutable, makes it possible to limit the risk of fraud.